Effect of gem‐Difluorination on the Key Physicochemical Properties Relevant to Medicinal Chemistry: The Case of Functionalized Cycloalkanes. Issue 19 (4th March 2022) - Holovach, Sergey; Melnykov, Kostiantyn P.; Skreminskiy, Artem; Herasymchuk, Maksym; Tavlui, Olha; Aloshyn, Danylo; Borysko, Petro; Rozhenko, Alexander B.; Ryabukhin, Sergey V.; Volochnyuk, Dmitriy M.; Grygorenko, Oleksandr O.
Abstract: Physico‐chemical properties important to drug discovery (p K a, Log P, and aqueous solubility), as well as metabolic stability, were studied for a series of functionalized gem ‐difluorinated cycloalkanes and compared to those of non‐fluorinated and acyclic counterparts to evaluate the impact of the fluorination. It was found that the influence of the CF2 moiety on the acidity/basicity of the corresponding carboxylic acids and amines was defined by inductive the effect of the fluorine atoms and was nearly the same for acyclic and cyclic aliphatic compounds. Lipophilicity and aqueous solubility followed more complex trends and were affected by the position of the fluorine atoms, ring size, and even the nature of the functional group present; also, significant differences were found for the acyclic and cyclic series. Also, gem ‐difluorination either did not affect or slightly improved the metabolic stability of the corresponding model derivatives. The presented results can be used as a guide for rational drug design employing fluorine and establish the first chapter in a catalog of the key in vitro properties of fluorinated cycloalkanes. Abstract : Fearless Fluorine : the effect of gem ‐diflurination on acidity/basicity (pKa ), lipophilicity (Log P ), aqueous solubility ( S w ), and metabolic stability (intrinsic clearance, CLint ) of functionalized C3 −C7 ‐cycloalkanes is established and compared to those of non‐fluorinated and acyclic counterparts. While the p K a values are varied similarly for the cyclic and acyclic series and can be explained by the inductive effect of the fluorine atoms, the Log P and S w trends are more complex. The CLint values are retained or slightly improved upon gem ‐difluorination.